Split Sentencing in Florida: Race/Ethnicity, Gender, Age, and the Mitigation of Prison Sentence Length - Lehmann, Peter S. (American journal of criminal justice, 2021)
Corresponding with the theoretical expectations of the causal attributions and focal concerns perspectives, a vast body of sentencing literature has shown that Black and Hispanic defendants, and specifically young minority males, are more likely than other offenders to receive incarceration sentences, longer prison terms, and punitive departures from sentencing guideline recommendations. To date, however, minimal research has examined racial/ethnic, gender, and age disparities in split sentencing, that is, the discretionary assignment of a sentence to both prison and post-release community supervision in lieu of a full prison term. Using data on felony offenders sentenced to prison in Florida circuit courts ( N = 193,513), these analyses show that Blacks and Hispanics, and particularly minority males, are less likely than Whites to receive a split sentence relative to a traditional prison sentence. Further, among female offenders only, racial/ethnic disparities are found to be weaker among young adults ages 18–20.